REALITAS SOSIAL DALAM SINETRON RAMADHAN: ANALISIS KRITIS TENTANG TAYANGAN SINETRON RAMADHAN DI STASIUN TELEVISI INDOSIAR - Ropingi Ropingi (Indonesian Journal of Dialectics, 2012)
This researchis based on the assumption that television has been used for mass communication process, because television has been integrating the texts, audios, and visuals in a massage.The advantages television can be displayitto representsa socialrealitymoretangible. But, social reality of television related bytendency and ideology of media makers.So, how was social reality showed?What is ideology of Ramadhan cinema discourse? This problem will be study by criticism approach.Critical discourse analysis from Norman Fairclough is used as method to research the discourse and ideology of social reality at Ramadhan soap opera. The main questions of this research was firstly how is social realityand the context’s presented as a discourse at Ramadhan soap opera? Secondly, how is the practice of discourse of Ramadhan soap opera? Thirdly, how is the socio-cultural context of ramadhan soap opera discourse?And the last question is what is the ideology of ramadhan soap opera?The result of this study shown that the social reality of religiousity, economy, and cultural, are attempt verballyand visually, but not supportedbygood of detail stories. Religious symbols visuallized in every detail of story but it is contradictory with religious values. Thepractice of discourse developed by market oriented mission. Ramadhan soap opera did not representthe social and cultural reality. Ramadhan soap opera is the part of the capitalistic  media industry. The ideology of the soap opera is to make money by seling violent, love stories, and pragmatism way of life.